ANALYSIS OF SOIL DYNAMICS AND GROUND MOVEMENT VULNERABILITY USING THE HVSR METHOD BASED ON MICROTREMOR MEASUREMENTS IN THE SEMPU AREA, PASURUAN - Yuansyah Dhaniar Ramadhan; Adedio Daniel Situmeang; M. Rizky Saputra; Safira Nur Cholisatin; Divana Zumrotul Asyfiya; Alif Haidar Safrian; Muhammad Nurul Fahmi; Madlazim Madlazim; Arie Realita (Indonesian Physical Review, 2026)
The Sempu Area, located in Cowek Village, Purwodadi Subdistrict, Pasuruan Regency, has a high potential for ground movement due to its lithological conditions, which consist of loose volcanic deposits and weathered sedimentary rocks, thereby increasing the risk of seismic wave amplification. This study aims to analyze the dynamics and soil vulnerability to ground movement phenomena using the Horizontal-to-Vertical Spectral Ratio (HVSR) method based on microtremor data. Data collection was conducted at 15 measurement points using a three-component seismograph, with a recording duration of 20 minutes per point. The data were analyzed using SeismoWin for signal filtering, Geopsy for extracting the fundamental frequency (f₀) and amplification values, and Surfer and ArcGIS for spatial visualization in the form of dominant frequency maps, amplification maps, and soil vulnerability index (Kg) distribution. The results showed that the dominant frequency values ranged from 2.75 to 5.92 Hz, with a maximum amplification value of 6.18. The most vulnerable zones were identified in the central part of the hamlet, specifically at points 10 and 14, which exhibited the highest Kg value of 14.12. These findings indicate the presence of significant local resonance zones arising from unconsolidated lithology, thereby increasing the risk of damage from seismic shaking. The implications of this study support land-use planning based on seismic microzonation and the development of more precise disaster mitigation strategies in areas prone to ground movement.